2020
DOI: 10.25301/jpda.291.19
|View full text |Cite
|
Sign up to set email alerts
|

Location of the Mental Foramen Using Volumetrically Rendered CBCT Images

Abstract: OBJECTIVE: To determine mental foramen location using volumetrically rendered Cone Beam Computed Tomography (CBCT). METHODOLOGY: This is a retrospective study composed of data from 200 scans of patients which were referred to the oral and maxillofacial radiology clinic. Localization was done bilaterally based on the relationship between the mental foramen and posterior teeth in their long axes. six possible position were identified (Position 1: anterior to the first premolar, Position 2: in line with the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…A similar study by Ahmed QN, et al reported the 50% male patients and 50% female patients [12]. Another study by Alfaleh WM reported the higher female patients 56% and lower male patients 44% [13]. A similar study by Zmyslowska-Polakowska E, et al reported the 52.7% male patients and 47.3% female patients [14].…”
Section: Discussionmentioning
confidence: 76%
“…A similar study by Ahmed QN, et al reported the 50% male patients and 50% female patients [12]. Another study by Alfaleh WM reported the higher female patients 56% and lower male patients 44% [13]. A similar study by Zmyslowska-Polakowska E, et al reported the 52.7% male patients and 47.3% female patients [14].…”
Section: Discussionmentioning
confidence: 76%
“…The most common places of the MF as described within many literatures which explain its situation have been found under the apex of the first premolar or consistent with the second premolar or in between them. Anatomical sites and gender differences have been reported in the literature (30) . The horizontal course of inferior alveolar nerve is an essential factor for detection of the situation of the site of mental foramen on panoramic radiograph.…”
Section: Discussionmentioning
confidence: 99%
“…The horizontal course of inferior alveolar nerve is an essential factor for detection of the situation of the site of mental foramen on panoramic radiograph. Studies have reported that in up to 25% of cases, essential structures such as the MF cannot be exactly determined when using panoramic radiographs (30) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations